Morpho‐palynological investigations of natural resources: A case study of Surghar mountain district Mianwali Punjab, Pakistan. Issue 7 (1st April 2019) - Qureshi, Muhammad Naeem; Talha, Naureen; Ahmad, Mushtaq; Zafar, Muhammad; Ashfaq, Shomaila
Abstract: Surghar mountain belt has comparatively less natural resources of floral diversity because it is composed of minerals of different kinds making it less favorable for the growth of different vegetation. The pollen morphology of some selected plants from Surghar belt Mainwali has been evaluated. The pollen grains were measured and demonstrated using scanning electron microscopy (SEM). The examined plant specimens have a difference in size, shape, polarity, and their exine ornamentation. The pollen taxa show a huge variation in size and sculpture. Pollen fertility has also been estimated, shows that the selected plants are well‐known in the Surghar belt. The need of the hour is to conserve these plants having a higher fertility rate to cope with the deforestation in an area. The conclusion does not favor theories in which deforestation results in fast growth in population. It shows that the irrational management and unlawful cutting down of woods neglected by the forest department are the main causes of deforestation in the mountain belt of Mianwali. The findings show the importance of morphological characteristics in the identification of natural resource species in the area. Abstract : The pollen morphology has been evaluated with the help of scanning electron microscopy (SEM). Pollen types are Subprolate, Prolate spheroidal and oblate spheroidal. High rate of pollen fertility shows the plants are well established in the area. Irrational management and unlawful cutting are the main causes of deforestation in the area.